"No Place for a White Man" : United Artists' Far East Department, 1922-1929. Issue 2 (1st August 2012) - Walsh, Michael
It has become a common practice to preface any remarks about the cinema of a culture of which one is not a member with the reminder that one speaks as an outsider with all the limitations that that implies. This article will attempt to reconstruct the position of the outsider, to explain the strategic and tactical considerations of U.S. film distribution in Asia. The recognition, within film studies, of the complexity involved in delimiting the national has gone hand in hand with an emergent emphasis on globalization as an increasingly important way in which production and distribution are organized in "late capitalism." However the film industry has always been heavily reliant on an international organization of its markets. To understand the current influences of transnationalism on both the film industry andon cultural production within the contemporary nation-state, we must contextualize this recent transnationalism within a historical perspective as part of an on-going historical process.